Enhanced characterization of oil sands acid‐extractable organics fractions using electrospray ionization–high‐resolution mass spectrometry and synchronous fluorescence spectroscopy. (30th March 2015) - Bauer, Anthony E.; Frank, Richard A.; Headley, John V.; Peru, Kerry M.; Hewitt, L. Mark; Dixon, D. George
Abstract: The open pit oil sands mining operations north of Fort McMurray, Alberta, Canada, are accumulating tailings waste at a rate approximately equal to 4.9 million m 3 /d. Naphthenic acids are among the most toxic components within tailings to aquatic life, but structural components have largely remained unidentified. In the present study, electrospray ionization high‐resolution mass spectrometry (ESI‐HRMS) and synchronous fluorescence spectroscopy (SFS) were used to characterize fractions derived from the distillation of an acid‐extractable organics (AEO) mixture isolated from oil sands process‐affected water (OSPW). Mean molecular weights of each fraction, and their relative proportions to the whole AEO extract, were as follows: fraction 1: 237 Da, 8.3%; fraction 2: 240 Da, 23.8%; fraction 3: 257 Da, 26.7%; fraction 4: 308 Da, 18.9%; fraction 5: 355 Da, 10.0%. With increasing mean molecular weight of the AEO fractions, a concurrent increase occurred in the relative abundance of nitrogen‐, sulfur‐, and oxygen‐containing ions, double‐bond equivalents, and degree of aromaticity. Structures present in the higher‐molecular‐weight fractions (fraction 4 and fraction 5) suggested the presence of heteroatoms, dicarboxyl and dihydroxy groups, and organic acid compounds with the potential to function as estrogens. Because organic acid compositions become dominated by more recalcitrant, higher‐molecular‐weight acids during natural degradation, these findings are important in the context of oil sands tailings pond water remediation. Environ Toxicol Chem 2015;34:1001–1008. © 2015 SETAC